Isolation, characterization, and in silico, in vitro and in vivo antiulcer studies of isoimperatorin crystallized from Ostericum koreanum. (1st January 2017) - Raza, Hussain; Abbas, Qamar; Hassan, Mubashir; Eo, Seong-Hui; Ashraf, Zaman; Kim, Daeyoung; Phull, Abdul Rehman; Kim, Song Ja; Kang, Sung Kwon; Seo, Sung-Yum
Abstract: Context: Ostericum koreanum (Maxim.) Kitagawa (Apiaceae) roots are traditionally used as an analgesic and antiulcer agent. However, the antiulcer potential of isoimperatorin isolated from O. koreanum has not yet been explored. Aim: To evaluate the antiulcer activity of isoimperatorin isolated from the roots of O. koreanum . Materials and methods: Isoimperatorin was isolated as cubic crystals by repeated column chromatography of the ethyl acetate fraction and structure was verified with 1 H NMR, 13 C NMR and high-resolution mass spectrometry (HRMS-FAB). The crystals obtained were analyzed with the single crystal X-ray method. The MTT assay was used to determine its cytotoxicity against chondrocytes at different concentrations (0.0–737.74 μM, 24 h). The in vivo antiulcer activity of isoimperatorin (40 mg/kg) was determined against ethanol-, indomethacin- and pyloric ligation-induced ulcers in Sprague-Dawley rats. Furthermore, the effect of isoimperatorin (0.0–737.74 μM, 24 h) on the expression of type II collagen in chondrocytes was determined using western blot method. The in vitro urease inhibitory activity of isoimperatorin (0–80 μM) and molecular docking was also performed against urease. Results and discussion: Isoimperatorin demonstrated significant inhibitory activity (IC50 36.43 μM) against urease as compared to the standard drug thiourea (IC50 33.57 μM) without cytotoxic effects. It provided 70.9%, 67.65% and 54.25% protection in ulcer models induced by ethanol, indomethacin and pyloric ligation, respectively. Isoimperatorin showed the highest expression level of type II collagen at 368.87 μM. The docking results confirmed strong binding affinity with the target protein. Conclusion: Isoimperatorin may be used to develop antiulcer drugs with decreased side effects.